THE IMPLEMENTATION OF COMMUNITY LANGUAGE LEARNING (CLL) IN TEACHING SPEAKING (A Qualitative Study at One of Universities in Cianjur) - Asep Saepuloh (Universitas Suryakancana, 2017)
AbstractSpeaking is one of important aspects of language. Speaking plays an important role in transfering English speaking skill to students as well as the key to the success of teaching learning process of speaking. There are many methods or approaches used by lecturers in the classroom in teaching speaking in university, they however considered not so effective in stimulating students to be more active in speaking and to have more bravery and self confidence to use their own English although they may make more mistakes. Based on the depicted reality, the researcher feels chalenged to know how is the implementation of Community Language Learning (CLL) method, to investigate its strengths and weaknesses, as well as to find out students’ difficulties in teaching s6peaking.This research entitled The Implementation of Community Language Learning (CLL) in Teaching Speaking. This research is conducted on the second semester students of English Education Study Program who are taking Speaking For General Communication II on the second semester students at one of universities in Cianjur. This research aims to know how the implementation of CLL and to investigate its strengths and weaknesses, as well as to find out students’ difficulties in learning speaking through CLL.This research uses qualitative method which employs several techniques in collecting the data. The data are obtained by conducting observation and interview. Keywords: Community Language Learning, teaching, and speaking